2018
DOI: 10.1016/j.jfoodeng.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HPCD batch treatments on enzyme inactivation kinetics and selected quality characteristics of cloudy juice from Golden delicious apples

Abstract: Cloudy apple juice has been treated by high pressure carbon dioxide (HPCD) as non-thermal technology to inactive polyphenoloxidase and pectinmethylesterase in batch mode. Stirring speed (from 200 to 600 rpm) induced an increase in the enzyme inactivation rate while a triple cycle of pressurization/depressurization led to the same enzyme inactivation efficiency. Enzyme inactivation kinetics were determined at different temperatures (from 35 to 45 ºC) and pressures (from 10 to 20 MPa). Data were described by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 32 publications
2
76
1
3
Order By: Relevance
“…The stability of enzyme structure is maintained by weak non‐covalent bonding including hydrophobic interactions, electrostatic forces, van der Waals forces, di‐sulfide and hydrogen bonding. Any modification to these forces could cause changes in the conformation and structure of an enzyme . A proposed mechanism of PPO inactivation by ultrasonic treatment is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of enzyme structure is maintained by weak non‐covalent bonding including hydrophobic interactions, electrostatic forces, van der Waals forces, di‐sulfide and hydrogen bonding. Any modification to these forces could cause changes in the conformation and structure of an enzyme . A proposed mechanism of PPO inactivation by ultrasonic treatment is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Any modification to these forces could cause changes in the conformation and structure of an enzyme. 41 A proposed mechanism of PPO inactivation by ultrasonic treatment is illustrated in Fig. 6.…”
Section: Inactivation Mechanism Of Ppo By Ultrasonic Treatmentmentioning
confidence: 99%
“…At 60ºC, no PME inactivation was observed at any of the treated volumes (power density ranged from 1.21 to 1.57 W/mL), even a slight increase was found, probably due to the release of enzyme bound to cell walls (Ertugay & Baslar, 2014). The greater stability of PME compared to PPO has been also found in thermal treatments and other non-thermal treatments such as HPCD (Illera et al, 2018) and it has been attributed to the more complex structure of PPO, with three or four subunits in higher plants, that makes it more susceptible to inactivation. Additionally, PME in fruit juices is more difficult to be effectively inactivated, since PME is bound to the plant cell wall, which contains natural stabilizing factors (Zhou, Zhang, Leng, Liao, & Hu, 2010).…”
Section: Effect Of Power Density On Enzyme Inactivation At Different mentioning
confidence: 96%
“…No previous studies have been found in the literature regarding the effect of this variable on fruit juices processed by TS. Finally, enzyme inactivation by TS was compared with previous results obtained by high pressure carbon dioxide (HPCD) treatment, as non-thermal technology (Illera et al, 2018), and with thermal treatment alone in the same temperature range. The effect of TS on other quality parameters of cloudy apple juice, such as particle size distribution (PSD), color and total polyphenols and hydroxymethylfurfural content has been also determined.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation